Health Equity and Financial Protection in Kenya - World Bank (Washington, DC, 2017)
The health equity and financial protection reports are short country-specific volumes that provide a picture of equity and financial protection in the health sectors of low-and middle-income countries. Topics covered include: inequalities in health outcomes, health behavior and health care utilization; benefit incidence analysis; financial protection; and the progressivity of health care financing. Kenya's government is committed to improving equity and financial protection in health by implementing the Second National Health Sector Strategic Plan (NHSSP II). Kenya spends 4.3 per cent (2009) of its gross domestic product (GDP) on health. This is lower than the average spending levels in other lower income countries in Africa, which spent an average of 6.5 per cent (2009) of their GDP on health. The functions of the health system in Kenya have historically been centralized through top-down decision-making and resource allocations. However, in the past decade Kenya has committed to decentralization of certain core functions to the district level. These include managing the health management system, making resource allocation decisions, and delivering health services. The central government maintains control over the majority of the key functions of the health system including staffing, contracting, and maintaining the national health information system. Kenya has a form of social insurance through the 40 year-old National Hospital Insurance Fund (NHIF). Employees in the formal sector are compulsorily insured and must make monthly contributions from their wages.